Effect of cerebrolysin on dopaminergic neurodegeneration of rat with oxidative stress induced by 3-nitropropionic acid - Calderón Guzmán David; Brizuela Norma Osnaya; Ortíz Herrera Maribel; Hernández García Ernestina; Barragán Mejía Gerardo; Juárez Olguín Hugo; Valenzuela Peraza Armando; Attilus Jonas; Labra Ruíz Norma (Acta Pharmaceutica)
The study tested the hypothesis that cerebrolysin protects the brain from free radicals in rats treated with 3-nitropropionic acid (3-NPA). To address this hypothesis, the levels of dopamine (DA) and some oxidative stress biomarkers were measured after administration of 3-NPA. Young male Fischer rats were treated for three days with cerebrolysin, 3-NPA or both substances. Their brains were extracted, and DA, lipid peroxidation (LP), glutathione (GSH), calcium, and H2O2 were measured using validated methods. In the cortex, hemispheres and cerebellum/medulla oblongata of the group treated with cerebrolysin and 3-NPA, the levels of DA and LP decreased. In addition, calcium and H2O2 levels decreased in the hemispheres of the same group, while GSH increased in cortex. The increased dopamine metabolism due to the administration of cerebrolysin led to increased formation of radical species and oxidative stress, especially when free radicals were generated by 3-NPA.